Batik Training as an Effort to Preserve Cultural Heritage at Molokiyah Arts and Culture Institutions - Oktaviani, Winda; Samad, Rita; Umanailo, Dwi; Nur Mawa, Dwi (PT. Anagata Sembagi Education, 2025)
The purpose of this activity was to enhance the capacity of human resources at the Molokiyah Arts and Culture Institute through creative batik training. The methods used included an approach and mentoring process that actively involved the partner institution the Molokiyah Arts and Culture Institute in every stage of the program, from planning to evaluation. The results of this community service activity showed a positive impact on the participants. Beginning with the introduction to the history, philosophy, raw materials, and tools used, as well as the basic techniques of hand-drawn batik, participants gained a deeper understanding of the batik-making culture. Training in techniques such as mencanting, coloring (mecolet), wax removal (melorod), and mastery of color-mixing skills contributed to increased creativity, precision, and self-confidence in their artistic creations. This batik-making activity not only preserves cultural heritage but also opens opportunities for economic and creative development in the future